Management of Patient with Closed Degloving in the Pelvic Region: a Case Series - Atmadja, Tessa Miranda; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: Degloving injuries in pelvis, torso and extremities present a challenge in wound management. Current management usually is the effort to provide wound coverage with split thickness skin graft (STSG). Problems arise in the wound bed preparation because the patient is not mobile, urine or feces contamination, and systemic problems such as anemia, hypoalbuminemia and sepsis. After wound coverage with STSG, problems arise during postoperative period caused by dificulty to maintain immobilization of the graft due to the location.Patients and Methods: In January to February 2012, 3 patients were admitted to Cipto Mangunkusumo hospital with degloving in the pelvic region. They were treated with delayed STSG.Results : The first patient underwent delayed STSG with a 75% take. The second patient was treated by serial STSG a month following hospital admission, the result was almost 90% take. The last patient underwent debridement and the wound was closed with STSG 10 days after admission, the result was only 50% take.Summary : Management of degloving patients should include adequate wound bed preparation with dressing that minimize infection and enhance good granulation tissue, maintain good systemic condition by providing adequate nutrition with care to albumin and electrolyte loss. Care should be given to prevent SIRS and sepsis. After wound coverage with STSG, modalities to immobilize the graft and maintain ideal environment for graft take have to be considered.